The Effectiveness of Using Origami Paper Folding Techniques in Improving the Fine Motor Skills of Children Aged 5-6 Years - Anisa Suci Hardini; Evie Palenewen; Fitri Anjarwati (Journal of Practice Learning and Educational Development, 2026)
This study aims to determine the effectiveness of using origami paper folding techniques in improving the fine motor skills of 5-6 year old children at Barunawati 3 Kindergarten in Samarinda. This study uses a quantitative approach with a pre experimental design, One Group Pretest Posttest Design. The sample used was total sampling, namely all 23 children in group B at Barunawati 3 Samarinda. The results of this study showed that the pretest score 50.10, categorized as developing, and after the treatment, the average posttest score was 75.43, categorized as developing as expected. The n-gain score obtained a value of 0.6 < 0.7 with a percentage of 67.05%. placing it in the moderate category, which means that the use of origami paper folding techniques in improving children’s fine motor skills is quite effective. The n-gain score results show an improvement in fine motor skill after treatment using the origami paper folding technique. Furthermore, the significance value obtained in the hypothesis test was 0.000 < 0.05, which means that the significance value is smaller than α = 0.05. the t-count value obtained was 41.356 and the t-table value obtained was 1.713, so it can be seen that t-count > t-table, namely 41.356 > 1.713.